Pengaruh Pengetahuan Produk dan Persepsi Kualitas Produk terhadap Keputusan Pembelian pada Kosmetik Organik - Indarto Candra Yoesmanam (BISMA (Bisnis dan Manajemen), 2018)
Knowledge of the people and businesses that increase would be so many impacts generated by used biohazard ingredients on cosmetics, resulting in the increasing the level of awareness of concern for the importance of the healty. It was addressed by marketers to perform marketing activities of the healty, so that the term green marketing. One of them by launching green products. Melilea is organic corporate the launching organic products in Indonesia. The innovation organic cosmetic,give impact on consumer behavior in increase the knowledge and perception of the products that can influence consumer purchase intentions.This research aims to analyze and discuss the influence of product knowledge and perception quality of product on organic cosmetics Melilea to purchase intentions. The type of this research is quantitative. The sampling technique that used was snawball sampling with sample size of 110 respondents. Statistics analysis used was multiple linear regression to know level of the influence.The results showed that the the influence of product knowledge and perception quality of product on purchase decision is 20.3% that value koefisian determination (adjusted R2), while the remaing 79.7% is influenced by other variables outside of research. In this study, dominant influence internet product knowledge with values is 0,291 while the perception quality of product variables with value is 0,122.